(untitled) (International Journal of Innovative Technologies in Economy, 2018)
Positive trends in economic growth over the past five years have not led to fundamental changes in the structure of the economy of the regions of the country, some regions lag significantly behind in terms of their socioeconomic development. In order to equalize the existing regional imbalances, it is necessary to assess the regional policy of the state and to modernize the development of the territories of the regions.